Genebank ‐ in vitro propagation of potato and sweetpotato. CIP‐SOP056 V 3.0 - Vollmer, R.; Panta, A.; Solis, R.; Manrique, N.; Anglin, Noelle L. (International Potato Center, 2020)
This procedure describes the in vitro multiplication of potato and sweetpotato germplasm for international and national germplasm distribution, as well as, in vitro conservation, phytosanitary, and cryopreservation activities.